GAMBARAN POTENSI INTERAKSI OBAT KORTIKOSTEROID PADA PASIEN PNEUMONIA ANAK DI INSTALASI RAWAT INAP RSUD ULIN BANJARMASIN - Widodo, Ridho Dwi; muliyani, muliyani; Isnani, Nazhipah; Zaini, Muhammad (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2023)
Pneumonia is mostly caused by bacterial, fungal, viral or parasitic microorganisms which cause the alveoli in the lungs to become inflamed and filled with fluid or mucus. Pneumonia occurs when parasites (pathogens) subvert or enhance the immune system, thereby causing inflammation or inflammation. in the lungs, the research method used in this study is a retrospective descriptive approach, namely an observational approach. This research was conducted at the Ulin Banjarmasin Regional Hospital, the population and samples using corticosteroids were 30 samples in 2020 - 2021 in pediatric pneumonia patients at the installation inpatient treatment at Ulin District Hospital, Banjarmasin. The variable used is a single variable, namely corticosteroid drug interactions in pediatric pneumonia patients at the Ulin Hospital Banjarmasin inpatient installation. (37%), with an age range of 0 - 5 years as many as 20 people (67%) and ages 6 - 12 years as many as 10 people (33%), the corticosteroid drug used was dexamethasone for 29 people (96.7%) and Methylprednisolone 1 prescriptions (3.3%), the incidence of drug interactions was 9 prescriptions (30%) and those that did not occur were 21 prescriptions (70%), with major levels being 0, moderate 0 and minor being 9 prescriptions (30%).